The Current Status of Government Early Childhood Care and Education Programs in Bahir Dar City Administration - Tola, Tiruwork Tamiru (Bahir Dar Journal of Education, 2020)
This study examined the current status of some government Early Childhood Care and Education (ECCE) Programs in Bahir Dar city Administration. Qualitative research approach, specifically, evaluation research was employed. The Ethiopia Education Sector Development Program V (ESDP V) was used as evaluation framework. Ewuqet Fana, Atsie Sertse Dingle, Felg Abay and Quliqual Meda preschools were the research sites. The data were collected from six teachers and three directors using available sampling technique. Semi-structured interview, observation and document analysis were employed to collect the data. Inductive analysis was applied to identify themes and analyze the data. The finding revealed that in the study programs, various ECCE modalities are being implemented some of which are not indicated in ESDP-V framework; shortage of classrooms, lack of trained teachers, large class size, lack of child sized chair and table, absence of water and sanitation facilities, and lack of play materials are found to be the major challenges affecting the status of the programs; school directors perceived that their preschools are providing low quality services and strategies outlined in ESDP V are not properly implemented. Finally, it was concluded that though government ECCE programs expanded to address the need of children from disadvantaged groups, they are serving these children with low status and lots of limitations. Thus, it is recommended that the government should give much emphasis to the quality status of the programs, amend its policy strategies and directly involve in the construction of ECCE program.